Pembuatan Video Profil Perpustakaan di Dinas Kearsipan dan perpustakaan Provinsi Sumatera Barat - Kurniawati, Era; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe kind of research this is qualitative with the methods descriptive. Data was gathered through observation and conducting interviews with outstanding librarians and pemustaka for the local office of chancery and libraries the province of west sumatra .As well as by assistance material the manner it should be has to do with video. Writing in the papers were intended to discuss steps that video production profile of the library and libraries in the chancery. west sumatra provinceThis study seeks to describe the stages of making a video of the profile of the library and libraries in the chancery west sumatra province. Based on an analysis data can be concluded that stages in making video library profile as follows: first, production in pre the done before the video consisting of invention an idea or ideas, sinopsis, treatment, storyboard, shooting the script, production production planning and preparation.Â Second, and hold what production developed at the praproduksi.Third, pascaproduksi end in the process of producing the video before video ready to served.Keyword: video, library